Associating Emergency Medical Services personnel’s workload, trauma exposure, and health with the cortisol, endocannabinoid, and N-acylethanolamine concentrations in their hair - Alexander Behnke (Scientific Reports, 2020)
Abstract In their line of duty, Emergency Medical Services (EMS) personnel are exposed to chronically stressful working conditions and recurrent traumatic events, which increase their risk for detrimental health outcomes. Here, we investigated whether this risk is due to altered regulation of the hypothalamus–pituitary–adrenal (HPA) axis and the endocannabinoid system. Therefore, 1 cm hair strands were collected from a cohort of 72 German EMS personnel in order to measure concentrations of cortisol, endocannabinoids [i.e., anandamide (AEA), 2-arachidonoylglycerol (2-AG)], and N-acylethanolamines [i.e., stearoylethanolamide (SEA), oleoylethanolamide (OEA), and palmitoylethanolamide (PEA)]. Rank correlation analyses were conducted to test associations of cortisol, endocannabinoid, and N-acylethanolamine concentrations with the EMS personnel’s workload, lifetime trauma exposure, and mental and physical health problems. We found a negative correlation between cortisol and 2-AG concentrations in hair. Higher hair cortisol was associated with higher workload. Reported traumatic stress during childhood and later in life as well as more severe depressive and physical stress symptoms were associated with elevated 2-AG, SEA, OEA, and PEA concentrations. Future longitudinal research needs to address the prospect of tracing biomolecular markers of glucocorticoid, endocannabinoid, and N-acylethanolamine activity as a predicting value of the long-term course of mental and physical well-being.